ANALISIS PENGENDALIAN KUALITAS PRODUK KORAN PADA PT. RADAR SULTENG MEMBANGUN DI KOTA PALU - NITAFIYAH, ZAHRO?IN (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to determine how the implementation of quality control using statistical aids is useful in an effort to control the level of product damage in the company. Quality control analysis is carried out using statistical tools in the form of check sheets and p control maps. Check sheets are used to present data to make it easier to understand data for the purposes of subsequent analysis. P control maps are used to monitor damaged products whether they are still in control or not.The results of the P control chart analysis show that the process has been carried out well. This can be seen in the final product quality control chart with the final number of CL values showing 0.0049, UCL 0.0091, LCL 0.0007 with a proportion of 0.0050 defects which means that the quality control process is within controlled limits because the value of the defect proportion is smaller than the UCL value